1978
DOI: 10.1016/s0006-3495(78)85353-3
|View full text |Cite
|
Sign up to set email alerts
|

Hapten-linked conformational equilibria in immunolglobulins XRPC-24 and J-539 observed by chemical relaxation

Abstract: The interaction of oligogalactan haptens with the murine myeloma proteins XRPC-24 and J-539 has been investigated by the fluorescence temperature-jump method. The relaxation spectrum is composed of two processes, the faster representing hapten assocaition and the slower a protein isomerization. In both cases the concentration dependence of relaxation times and amplitudes was consistent with the general mechanism formulated by Lancet and Pecht (1976, Proc. Natl. Acad. Sci. U.S.A. 73:3549), in which the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Bi-or triphasic binding kinetics was first described for anti-hapten antibodies (35,37,41,42), but have not previously been described for antibody-protein associations. The observation that anti-DNP myeloma proteins exhibit biphasic or triphasic kinetics is particularly relevant, as the antibody MOPC460 expresses V H 36-60 and Vκ23 genes and thus is structurally related to the anti-HEL antibodies described here (43,44).…”
Section: Evidence For a Two-mentioning
confidence: 99%
“…Bi-or triphasic binding kinetics was first described for anti-hapten antibodies (35,37,41,42), but have not previously been described for antibody-protein associations. The observation that anti-DNP myeloma proteins exhibit biphasic or triphasic kinetics is particularly relevant, as the antibody MOPC460 expresses V H 36-60 and Vκ23 genes and thus is structurally related to the anti-HEL antibodies described here (43,44).…”
Section: Evidence For a Two-mentioning
confidence: 99%
“…To our knowledge, no triphasic antibody-hapten reaction has previously been reported. The absence of a third phase in earlier studies (10)(11)(12)(13)(14) has been attributed variously to experimental difficulties in detecting very short relaxation times or low amplitudes, or to the system approximating a limiting case of Mechanism I. The operation of Mechanism I in these cases was inferred from quantitative incongruities in other parameters, such as independently measured equilibrium constants or relaxation amplitudes.…”
mentioning
confidence: 99%
“…Kinetic analysis avoids this particular ambiguity. Indeed, studies on several myeloma proteins have demonstrated kinetically distinct conformational isomers (10)(11)(12)(13). It could be argued that myeloma cells have an uncertain ontogeny and are not subject to the immune maturation mechanisms encountered in a bona fide antigenic response; however, similar kinetic behavior was reported for an anti-fluorescein hybridoma (14).…”
mentioning
confidence: 99%
“…In some studies (16,17), no conformational changes were observed upon binding of a small ligand. In others, conformational alterations correlated with hapten or antigen binding have been inferred on the basis of increased conformational stability ofthe Fab (18,19), decreased solubility (20), changes in the accessibility of bound hydrogens for solvent exchange (21), and results of numerous spectroscopic studies (22)(23)(24)(25)(26). In crystallographically based studies of conformational changes in the light-chain dimer Mcg, it was concluded that ligand binding caused alterations in both VL-VL and CL-CL interactions (27,28).…”
mentioning
confidence: 99%